A multistudy examination of the complementarity dimension of the coach-athlete relationship - Felton, L.; Jowett, S.; Begg, C.; Zhong, X. (Sport, Exercise, and Performance Psychology, 2021)
This multistudy aimed to examine the complementarity dimension of the coach-athlete relationship in relation to individual and group outcomes, specifically well-being and cohesion. Self-report data were collected from athletes in the United Kingdom (n = 304). In Study 1 (n = 106), mediation analysis demonstrated significant indirect effects between direct- and meta complementarity and vitality via basic psychological needs satisfaction. In addition, a significant direct effect between direct complementarity and vitality was also seen, independent of the indirect effect. In Study 2 (n = 198), mediation analysis demonstrated significant indirect effects between direct- and meta complementarity and task and social cohesion via the basic psychological needs. A significant direct effect between meta complementarity and task cohesion was also identified, independent of the indirect effects. No direct or indirect effects were observed for reciprocal complementarity. Findings highlight the importance of complementarity, and satisfaction of the basic psychological needs, within the coach-athlete relationship for enhancing athletes` feelings of well-being and cohesion